2017
DOI: 10.1177/0009922817728697
|View full text |Cite
|
Sign up to set email alerts
|

Resident Documentation of Social Determinants of Health: Effects of a Teaching Tool in the Outpatient Setting

Abstract: Social determinants of health (SDH) significantly affect the health of children and thus, screening is important in pediatric primary care. We assessed the use of a formal social history taking tool after a 2-phase intervention. The first phase (P1) was a teaching module describing SDH and community resources and the second phase (P2) consisted of visual reminders to use the tool. Patient charts (n = 322) were reviewed pre- and postintervention. Residents had higher documentation rates of Women, Infants, and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(50 citation statements)
references
References 34 publications
0
50
0
Order By: Relevance
“…Fifty-eight studies were conducted with primary care patients, [29][30][31][72][73][74]76,[78][79][80][81][82][83][84][85][86][87][88][89] 4 took place in a specialty clinics, 32,71,75,77 1 took place in urgent care, 27 and 3 took place across multiple settings (eg, primary, specialty, and urgent care). 26,28,90 Majority of studies reported including academic sites (n = 40), 29,[34][35][36][37][38][39][41][42][43][44][47][48][49][50][51][52][53][54][55][56][57][58]…”
Section: Characteristics Of Sources Of Evidencementioning
confidence: 99%
“…Fifty-eight studies were conducted with primary care patients, [29][30][31][72][73][74]76,[78][79][80][81][82][83][84][85][86][87][88][89] 4 took place in a specialty clinics, 32,71,75,77 1 took place in urgent care, 27 and 3 took place across multiple settings (eg, primary, specialty, and urgent care). 26,28,90 Majority of studies reported including academic sites (n = 40), 29,[34][35][36][37][38][39][41][42][43][44][47][48][49][50][51][52][53][54][55][56][57][58]…”
Section: Characteristics Of Sources Of Evidencementioning
confidence: 99%
“…The use of various tools as memory aids and to trigger reminder of importance of documenting the paediatric social history as part of a child’s medical record may be helped by the use of standardised tools such as IHELLP (Income, Housing, Education, Legal Status, Literacy, Personal Safety). This tool has been shown to significantly improve documentation of the paediatric social history [ 45 ]. This tool triggers the interviewer to inquire about income supports, housing, education, legal and immigration status, language and personal safety.…”
Section: Discussionmentioning
confidence: 99%
“…Due to these issues of using geographic measures to predict transplant outcomes, alternative strategies must be considered for evaluating socioeconomic disparities in transplantation. The implementation of systematic screening for social determinants of health (SDH) has been previously described in primary care settings [29, 30], and could be added to reporting requirements for transplant candidate registration. While such screening could provide accurate patient-level SES data, standardized collection of SDH in clinical settings entails its own challenges, including a lack of consensus on best measurements and data collection practices, lack of collaboration between health systems and social services organizations, and technological challenges to capturing and retaining these data [31].…”
Section: Discussionmentioning
confidence: 99%